EDUKASI PEMBELAJARAN MATEMATIKA KEPADA SISWA KELAS 1 SEKOLAH DASAR NEGERI 4 TIGA, KECAMATAN SUSUT, BANGLI - Gusi Putu Lestara Permana; Sefia Subrata; I Made Wirya Darma; I Wayan Sutama (Jurnal Pengabdi, 2023)
Elementary education or elementary school is the initial momentum for children to improve their abilities, from elementary school they get learning immunity which then becomes a habit for them to do in the future. Learning language in elementary schools is an activity to equip students from the start on an ongoing basis so that students have discipline in thinking and speaking, most language teachers are not very aware of the importance of coaching writing training so that it causes students to have low writing creativity. Based on the results of observations at SDN 4 Tiga, Bangli, it was found that students in grade I had low creativity and writing skills. Keywords: Education, Elementary School, Students